Development and validation of an endoscopic index of the severity for Crohn's disease: a prospective multicentre study. Groupe d'Etudes Thérapeutiques des Affections Inflammatoires du Tube Digestif (GETAID). Issue 7 (July 1989) - Mary, J Y; Modigliani, R
Abstract : The aim of this study was to develop and validate an endoscopic index for assessing the severity of Crohn's disease. Endoscopic findings were prospectively collected by a multicentre group in 75 patients with Crohn's colitis according to a previously validated procedure. The presence of nine preselected lesions was recorded in the following segments (1) rectum, (2) sigmoid and left colon, (3) transverse colon, (4) right colon, and (5) ileum. In addition the extent of the diseased and ulcerated areas were estimated in each segment. These segmental data were recorded on a standard form, together with the endoscopist's global estimate of lesion severity. A stepwise multiple regression was used to derive an index which was correlated with the endoscopist's global evaluation of lesion severity. Four mucosal lesions: deep and superficial ulcerations, ulcerated and non-ulcerated stenosis, and both estimates of extent involved were selected and weighted to obtain a Crohn's Disease Endoscopic Index of Severity which correlated with the endoscopist's global appraisal of lesion severity (r = 0.83). This index was then prospectively shown to be valid in a further series of 113 colonoscopies (r = 0.81). The index was calculated in 54 patients with active Crohn's disease, before and at the end of a course of corticosteroids: index variations correctly reflected changes in colitis severity as evaluated by the endoscopists (r = 0.72). For endoscopists familiar with the data collection procedure, this Crohn's Disease Endoscopic Index of Severity should be of value in the follow up of patients, especially in clinical trials.